1991
DOI: 10.1017/s095026880004855x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of arboviruses from the Sultanate of Oman

Abstract: SUMMARYSentinel herds and a vector surveillance system were used to identify the presence of arboviruses in Oman. Two strains of bluetongue virus (BTV) serotype 4 and two strains of Akabane virus, were isolated and identified. Both BTV isolates and one Akabane virus isolate came from goats while the second Akabane isolate came from Culicoides imicola. This is the first isolation of an Akabane virus from Culicoides in Arabia. Vector competence studies with the Oman viruses in laboratory reared C. variipennis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Culicoides midges were suspected to be responsible for this fast spread of SBV because they are known vectors for several related viruses (e.g. AKAV) (St George et al ., ; Al‐Busaidy & Mellor, ; Bryant et al ., ; Yanase et al ., ). Several studies using field‐collected midges have detected SBV in C. obsoletus complex, C. chiopterus and C. dewulfi midges (De Regge et al ., ; Rasmussen et al ., ; Goffredo et al ., ; Elbers et al ., , ; Larska et al ., , ) and a vector competence study has shown the replication and dissemination of SBV in C. sonorensis (Veronesi et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Culicoides midges were suspected to be responsible for this fast spread of SBV because they are known vectors for several related viruses (e.g. AKAV) (St George et al ., ; Al‐Busaidy & Mellor, ; Bryant et al ., ; Yanase et al ., ). Several studies using field‐collected midges have detected SBV in C. obsoletus complex, C. chiopterus and C. dewulfi midges (De Regge et al ., ; Rasmussen et al ., ; Goffredo et al ., ; Elbers et al ., , ; Larska et al ., , ) and a vector competence study has shown the replication and dissemination of SBV in C. sonorensis (Veronesi et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of SBV has in the meantime also been confirmed in the Netherlands, Belgium, United Kingdom, France, Luxembourg, Italy and Spain. The rapid and wide expansion of SBV, together with the knowledge that related viruses like Akabane and Aino virus are spread by midges and mosquitoes (St George et al., ; Al‐Busaidy and Mellor, ; Bryant et al., ; Yanase et al., ), led to the hypothesis that also SBV might be spread by these vectors. We analysed pools of midges caught in Belgium to identify putative local vectors for SBV.…”
Section: Introductionmentioning
confidence: 99%
“…Vector competence studies for these arboviruses are most complete for AKAV, particularly in Australia where the role of Culicoides brevitarsis in transmitting and spreading the virus has been characterized in detail [7], [8]. Incidence of AKAV in field collected Culicoides has also been studied in Israel [9], [10], the Oman [11] and the Republic of South Africa [12], where the major Afro-tropical arbovirus vector Culicoides imicola is believed to play a primary role in transmission.…”
Section: Introductionmentioning
confidence: 99%